2023
DOI: 10.1002/smll.202305300
|View full text |Cite
|
Sign up to set email alerts
|

Shape Anisotropy‐Governed High‐Performance Nanomagnetosol for In Vivo Magnetic Particle Imaging of Lungs

Saumya Nigam,
Jeotikanta Mohapatra,
Ashley V. Makela
et al.

Abstract: Caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), coronavirus disease 2019 (COVID‐19) has shown extensive lung manifestations in vulnerable individuals, putting lung imaging and monitoring at the forefront of early detection and treatment. Magnetic particle imaging (MPI) is an imaging modality, which can bring excellent contrast, sensitivity, and signal‐to‐noise ratios to lung imaging for the development of new theranostic approaches for respiratory diseases. Advances in MPI tracers would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…However, they studied a single sample representative of each condition, and the four studied samples had a narrow range in shape. Another suggested that shape anisotropy of ∼50 nm long and ∼8 nm wide nanorods improves their MPI performance . However, this study provided very limited physical and magnetic characterization of the nanoparticles used, and the claim is based on comparison between ∼50 nm long nanorods and ∼13 nm spherical nanoparticles.…”
Section: Resultsmentioning
confidence: 93%
“…However, they studied a single sample representative of each condition, and the four studied samples had a narrow range in shape. Another suggested that shape anisotropy of ∼50 nm long and ∼8 nm wide nanorods improves their MPI performance . However, this study provided very limited physical and magnetic characterization of the nanoparticles used, and the claim is based on comparison between ∼50 nm long nanorods and ∼13 nm spherical nanoparticles.…”
Section: Resultsmentioning
confidence: 93%
“…Recently, we explored oleylamine as a multi-functionalizing agent to synthesize nanoparticles with controlled shapes and desired stoichiometry. Figure 8 shows Fe 3 O 4 nanoparticles of different shapes synthesized via the thermal decomposition of iron (III) acetylacetonate and the chemical reduction of FeOOH nanorods using oleylamine as solvent and surfactant [75,112,113].…”
Section: Shape Anisotropy: Change Of Shapementioning
confidence: 99%
“…Iron oxide nanoparticles, which have unique magnetic properties, exhibit outstanding performance and significant potential for use in biomedical applications, such as magnetic resonance imaging and targeted drug delivery. 33 As a delivery system, iron oxide nanoparticles can transport antigens to the immune system or serve as immune adjuvants to enhance antigen processing. To prevent the aggregation and oxidation of magnetic nanoparticles after synthesis, these nanoparticles can be coated with single-layer ligands, polymers, combinations of polymers and biomolecules (phospholipids and carbohydrates), or inorganic materials (silica and gold).…”
Section: Nanomaterials Used As Nanovaccinesmentioning
confidence: 99%